Soil Organic Matter in Biomass Determinations - Jha, M. N.; Rathor, A. K. S. (Indian Forester, 1984)
Soli incorporated organic matter is invariably left out from biomass determinations. The overwhelming importance of soil organic matter suggests that this fraction should be included in the biomass determinations. The value of Soil Organic Matter and biomass obtained under various forest species have been discussed.